The adoption of the Islamic banking service: non-Muslim communities perception and intention - Kartika, Erawati; Santoso, Ignatius Hari (Sebelas Maret Business Review, 2022)
this study aims to reconfirm the theory regarding the intention to adopt the services of Islamic banking institutions. Respondents used in this study were obtained through the snowball technique as many as 89 non-Muslim communities. the sample was taken using the snowball technique with the main criteria, the respondent had never used the services or products of an Islamic banking institution. This research proves that only the perceived quality of information can have a significant effect by using the constructs of perceived quality of information, perceived benefits, and subjective norms. Previously, the data was analyzed using the bootstrapping technique on the Smart PLS application. One of the interesting findings from this research is that even though the respondents did not understand in depth about the operational mechanisms of Islamic banking institutions, they were informed that the features and explanations of each product offered through the media could be well understood. The main limitation in this study is, of course, the number of samples used. In addition, further research is also needed using more specific questionnaire items on one of the Islamic banking products or services.